2021
DOI: 10.1093/fqsafe/fyaa030
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological assessment of street foods at the point of sale in Maputo (Mozambique)

Abstract: In Mozambique, as in other developing countries, the sale of street food is a source of income for thousands of unemployed families. However, the safety of these types of foods is a serious problem, given their frequent association with food-borne outbreaks. The aim of this study was to assess the microbiological quality and safety of street food sold in the main streets and informal markets of Maputo, the capital of Mozambique. From 83 different vendors selling different types of foods, 83 samples of ready-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 25 publications
6
27
0
2
Order By: Relevance
“…GAS had higher values of pH, crude protein, fat, fibre, ash, and energy whereas UAS were higher in moisture and crude carbohydrate contents. MAB/TAPC which corroborates earlier literature reports [12,19], but exceeded limits for coliforms (E. coli inclusive) for street vended foods. However, investigators reported much higher counts when Ugba (Pentaclethra macrophylla) and Ogiri (Ricinus comminus) were incorporated into the dish [8,37].…”
supporting
confidence: 90%
See 2 more Smart Citations
“…GAS had higher values of pH, crude protein, fat, fibre, ash, and energy whereas UAS were higher in moisture and crude carbohydrate contents. MAB/TAPC which corroborates earlier literature reports [12,19], but exceeded limits for coliforms (E. coli inclusive) for street vended foods. However, investigators reported much higher counts when Ugba (Pentaclethra macrophylla) and Ogiri (Ricinus comminus) were incorporated into the dish [8,37].…”
supporting
confidence: 90%
“…The high percentage frequency of occurrence of E. coli and coliforms in African salad is phenomenal and consistent with those found in traditional RTE foods in Nigeria and other developing countries [12,24,25,38,39]. Such levels of contamination is suggestive of poor handling, sanitation and possible faecal pollution.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Maputo has very diverse cultural and ethnic groups resulting from the country’s ethnic diversity and foreign immigrants from central African countries [ 27 , 28 ]. The administrative division of Maputo consists of seven municipal districts [ 28 , 29 ]. This study focused on four of them (Nlhamankulu, KaMaxaquene, KaMavota, and KaMubukwana) because of their abundant street selling activities [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The administrative division of Maputo consists of seven municipal districts [ 28 , 29 ]. This study focused on four of them (Nlhamankulu, KaMaxaquene, KaMavota, and KaMubukwana) because of their abundant street selling activities [ 29 ].…”
Section: Methodsmentioning
confidence: 99%